Women Engineers’ Self-Efficacy And Career Persistence: The Mediating Roles Of Job Crafting And Subjective Career Success - Krishnamoorthy, Lalitha (2021)
Engineering is one of the fields considered male-dominated and a non-traditional profession for women. Hence, many studies have focused on barriers that prevent women’s progress in engineering education and career domain. Little attention has been directed to those women engineers who persist despite the barriers. Guided by the human agency approach and drawing on social cognitive career theory and job demands-resources theory, this study focuses on two individual factors; job crafting behaviour and subjective career success (career satisfaction and satisfaction with work-life balance) as the influential variables explaining women engineers’ career persistence. A serial multiple mediator model was developed to examine the roles of job crafting and subjective career success as the underlying mechanism linking self-efficacy to career persistence. The research hypotheses were assessed using partial least squares structural equation modelling (PLS-SEM) with bootstrapping. Using a purposive sampling technique, data were collected through a survey method from a sample of women engineers employed in manufacturing organisations in Malaysia. A total of 156 data were analysed using PLS-SEM. The results of the study indicate that job crafting and subjective career success (career satisfaction and satisfaction with work-life balance) fully mediate the effect of self-efficacy on career persistence. Overall, this study contributes to the utility of the social cognitive career theory and job demands-resources theory among a sample of women engineers.